Pattern Recognition, Hypotheses Generation, and Auditor Performance in an Analytical Task - Bedard, Jean C.; Biggs, Stanley F. (The Accounting Review, 1991)
[Professional standards for analytical procedures call for auditors to hypothesize likely causes of unexpected patterns in financial statement balances and to develop plans to investigate (SAS 56). Therefore, audit efficiency and effectiveness depend on competency in recognizing patterns in financial data and in hypothesizing likely causes of those patterns to serve as a guide for further testing. Yet our knowledge of how well auditors accomplish these crucial steps has been limited by the difficulty of developing research tasks with criteria for evaluating auditor performance. The purpose of this study is to relate processes of pattern recognition and hypothesis generation to quality of performance in an analytical task. To accomplish this purpose, we conducted a laboratory study in which 21 auditors were asked to think aloud while performing an analytical procedures task. The case contained a seeded error that caused a fairly complex pattern of discrepancies between projected and unaudited financial ratios and balances. Think-aloud verbal protocols provided a trace of subjects' reasoning processes, and the seeded error provided an outcome criterion to evaluate the hypotheses they generated. This design supplies evidence needed to evaluate pattern recognition and hypothesis generation processes that lead to correct and incorrect outcomes. Results indicated that three auditors made acquisition errors and four failed to combine crucial cues into a pattern. Of the 14 auditors who recognized the pattern, six proposed a hypothesis consistent with the pattern. Thus, hypothesis generation was the stage at which process errors most frequently occurred, and the least experienced auditors had the most difficulty at that stage. Specific process problems that inhibited generation of a correct hypothesis included: addressing only part of a recognized pattern, and/or fixating on a certain error type. Thus, protocol analysis allowed insight into which stages in the process proved most difficult for the auditors and why, providing a focus for further research and decision aid development. This research responds to the call for inclusion of criterion outcomes in audit judgment research (e.g., Libby 1981; Ashton 1982; Biggs 1985; Davis and Solomon 1989). The importance of criterion outcomes can be seen in the advances made in decision research in medicine (e.g., Johnson et al. 1982; Patel and Groen 1986; Lesgold et al. 1988). and physics (e.g., Chi et al. 1982; Robertson 1990). In medicine especially, the ability to relate diagnostic processes to outcome quality has contributed to the theory and practice of medical decision making (Kassirer 1989) in ways that have been unavailable in auditing.]